Numerical simulation of debris flow caused by Bashkara Glacier lake outburst flood in 2017 - A. S. Solodova; D. A. Petrakov; K. A. Puganov (Лëд и снег)
Glacier lake outburst floods (GLOFs) are among the most destructive natural hazards in high mountain areas. Mathematical modeling can help to assess the potential consequences of such outbursts, delineate hazard zones, and calculate characteristics of debris flows and floods. The study is focused on the Lake Bashkara outburst on September 1, 2017, forming a stony debris flow with a total volume of about 1*106 m3. The availability of extensive data on this outburst allows to simulate the event using the r.avaflow program. The software can account for up to three phases in the flow: liquid, solid and fine solid. In our case the number of phases was reduced to two: liquid and solid. The software utilizes the volume of entrained material, flow parameters, and pre- and post- GLOF Digital Elevation Models (DEMs) obtained by previous researchers. The results were compared with actual data on the outburst and previous numerical simulations. The limits of the debris flow hazard zone, depth values, flow speeds (averaging 6 m/s), and travel time to different control points correlate well with previous simulations and eye-witness estimates. Due to the involvement of solid material, the calculated values of flow speed and depth increased slightly comparatively to previous estimates. This work is the first attempt to calculate the pressure and kinetic energy of the flow for different sections in the channel, and to assess the amount of eroded and accumulated material, changed the terrain after the GLOF. The obtained inundation zone almost replicates the observed boundaries delineated using post-GLOF Pleiades image on September, 3. The tested model, r.avaflow, can be applied in the Mt. Elbrus region to assess the dynamics and impact zones of stony debris flows initiated by lake outbursts.